2021
DOI: 10.1080/10903127.2021.1873472
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Nontrauma Patients Receiving Prehospital Blood Transfusion with the Same Triggers as Trauma Patients: A Retrospective Observational Cohort Study

Abstract: While prehospital blood transfusion (PHBT) for trauma patients has been established in many services, the literature on PHBT use for nontrauma patients is limited. We aimed to describe and compare nontrauma and trauma patients receiving PHBT who had similar hemodynamic triggers. Methods. We analyzed 3.5 years of registry data from a single prehospital critical care unit. The PHBT protocol included two packed red blood cell units and was later completed with two freeze-dried plasma units. The transfusion trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…Nearly half of the patients receiving PHBT were non-traumatic, with the most common reason being gastrointestinal hemorrhage. Previous studies have reported the non-traumatic group being anywhere from 22-68% of the patients receiving PHBT and gastrointestinal hemorrhage being the most common reason [10,12,14,15,16]. The patient characteristics observed in our study closely echo previous research.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Nearly half of the patients receiving PHBT were non-traumatic, with the most common reason being gastrointestinal hemorrhage. Previous studies have reported the non-traumatic group being anywhere from 22-68% of the patients receiving PHBT and gastrointestinal hemorrhage being the most common reason [10,12,14,15,16]. The patient characteristics observed in our study closely echo previous research.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the median delay would have been around 115 minutes from start of the emergency call to arrival to the hospital. Similar delays have been reported also by Lyon et al [2] 114 min delay, Vuorinen et all [14] 103 min delay and Ångerman et al [12] 97 min delay for non-traumatic patients and 83 min for traumatic. In this study, the PHBT was started median 54 minutes (IQR 38) from the emergency call and for trauma patients the median time was 51 minutes and for non-traumatic 54 minutes.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, non-traumatic hemorrhaging patients can also form a significant group that could benefit from prehospital transfusions [ 10 12 ]. Causes for non-traumatic hemorrhaging can include different reasons for postoperative complications, gastrointestinal hemorrhaging, and obstetric and gynecological emergencies.…”
Section: Introductionmentioning
confidence: 99%